2022
DOI: 10.12998/wjcc.v10.i16.5470
|View full text |Cite
|
Sign up to set email alerts
|

Rare case of hepatocellular carcinoma metastasis to urinary bladder: A case report

Abstract: BACKGROUND Hepatocellular carcinoma (HCC) is a primary liver cancer with high prevalence and mortality. There are many cases of advanced HCC at the time of diagnosis. Treatment methods and prognosis are different depends on whether metastasis is present. Thus, it is necessary to make an accurate evaluation at the time of diagnosis. Extrahepatic metastases of HCC usually occur through hematogenous spread or through adjacent organs such as the peritoneum. Metastasis to the urinary bladder alone is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Compared to the two previous cases, 3,4 our patient was diagnosed with a bladder tumor with advanced-stage HCC. Chung et al 5 also reported a case of advanced HCC with bladder metastasis.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Compared to the two previous cases, 3,4 our patient was diagnosed with a bladder tumor with advanced-stage HCC. Chung et al 5 also reported a case of advanced HCC with bladder metastasis.…”
Section: Discussionmentioning
confidence: 54%
“…Compared to the two previous cases, 3,4 our patient was diagnosed with a bladder tumor with advanced‐stage HCC. Chung et al 5 .…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations